Quantitative Studies on Halophilic Pathogenic Vibrios in Fish and Fish Products - Smitha, N R; James, Leejee; Iyer, T.S.G.; Sanjeev, S (Fishery Technology, 2025)
One hundred and thirty samples consisting of iced, block frozen and individually quick frozen (IQF) fish and fish products collected from landing centres, markets and fish processing factories situated in and around Cochin were examined for the incidence of halophilic pathogenic vibrios by using MPN method. Halophilic pathogenic vibrios were isolated from 72% of iced samples, 40.4% of block frozen samples and 29.2% of IQF samples. In general, 51.5% of the samples was found to be positive for halophilic pathogenic vibrios. Vibrio cincinnatiensis was found to be the dominant species isolated from different fish and fish products (incidence 30%, load varied from <1- 930 MPN g-1) followed by V. alginolyticus (25.4%, <1-360 MPN g-1), V. vulnificus (16.9%, <1- 530 MPN g-1), V. parahaemolyticus (8.5%, <1-9.1 MPN g-1), V. metschnikovii (4.6%, <1-30 MPN g-1), V. furnissii (2.3%, <1-30 MPN g-1 ), V. fluvialis (0.8%, <1 MPN g-1) and V. damsela (0.8%, <1- 3.6 MPN g-1). IQF samples showed the lowest incidence of halophilic pathogenic vibrios. Considering the seafood export potential of India, incidence of halophilic pathogenic vibrios in fish and fish products is a matter of serious concern.